An overview on the role of telomere , telomerase in degenerative diseases and cancer - Churong Li; Yin Gang (International Association of Physical Chemists (IAPC), 2015)
Telomerase maintains the length of telomeric DNA at the end of chromosomes; stabilizes the functions of chromosomes, protects the structure of chromosome DNA and regulates normal cell growth. The length and stability of telomeres determine the cellular lifespan, furthermore, they correlate with cellular aging and carcinogenesis. Researches on the role of telomerase in degenerative diseases and cancers show that it regulates cellular senescence in degenerative diseases. Although telomerase is not an oncogene, it does make tumor cells immortal by maintaining the stability of telomeric DNA. Telomerase-based therapies have become a hotspot in new anticancer and degenerative diseases treatments. This review aims to provide a comprehensive understanding of the role of telomerase and telomere in cellular senescence and cancer.